Analisis Pengaruh Penerapan “Sistem Informasi Manajemen (SIMRS) Terhadap Kinerja Karyawan Rumah Sakit Permata Depok Jawa Barat” Menggunakan Metode Regresi Linier Sederhana - RYAN ADHI WIBOWO (Reputasi: Jurnal Rekayasa Perangkat Lunak, 2022)
This research was conducted with the aim to determine the effect of the implementation of the Hospital Management Information System (SIMRS) on the performance of the employees of Permata Depok Hospital, West Java. This research was conducted in Permata Depok Hospital. This study uses a descriptive quantitative approach. The population in this study are all employees who are directly related to SIMRS. Sampling was done by using proportional random sampling technique, with a sample size of 50 respondents. Data collection techniques using a questionnaire. While the data analysis technique used is simple linear regression analysis. The results showed that the simple linear regression analysis test results showed that sig 0.05 with a sig value of 0.000 then Ho was rejected. This is also in accordance with the results of the determinant coefficient test which shows that the R Square value is 0.85 which can be stated that there is an influence between SIMRS on employee performance of 72.25%. The results of this study have the implication that SIMRS is one of the factors that can affect employee performance